2020
DOI: 10.1007/s10816-020-09484-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Reconstruction of Paleolithic Fires in the Chauvet-Pont d’Arc Cave (Ardèche, France)

Abstract: The Chauvet-Pont d'Arc Cave (Ardèche, France), famous for its remarkable rock art, also contains unique thermal-alterations such as rock spalling and color changes on the walls. These alterations resulted from intense fires that have not been observed in the other decorated caves thus far discovered. The functions of these unusual fires challenge archaeologists. To characterize these combustions, we used a numerical tool, previously validated with experimental data, to study the thermo-alterations in the Megac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…To solve this problem, and as a hypothesis based on the numerical data obtained after the simulation of the fires in the Chauvet Cave, it has been observed that large fires with high flames favor the expulsion of gases through convection currents, as well as develop an optimal thermal stratification to allow human occupancy in a cave during the operation of the fire. Because polluting gases are deposited in the upper area of the chamber above the flame, they leave a toxicity-free space that is large enough to be walked by humans and is slightly crouched [ 2 , 3 , 49 ]. Following this interpretation, in Nerja Cave, we have suggested using supports (for example, speleothems) to lift the flame and concentrate the smoke in the upper part of the cave, using a smaller volume of wood fuel than in the previous case [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To solve this problem, and as a hypothesis based on the numerical data obtained after the simulation of the fires in the Chauvet Cave, it has been observed that large fires with high flames favor the expulsion of gases through convection currents, as well as develop an optimal thermal stratification to allow human occupancy in a cave during the operation of the fire. Because polluting gases are deposited in the upper area of the chamber above the flame, they leave a toxicity-free space that is large enough to be walked by humans and is slightly crouched [ 2 , 3 , 49 ]. Following this interpretation, in Nerja Cave, we have suggested using supports (for example, speleothems) to lift the flame and concentrate the smoke in the upper part of the cave, using a smaller volume of wood fuel than in the previous case [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These researchers detected through thermoluminic analysis of the heated walls and an experimental approach that the temperatures reached by the walls of Chauvet Cave (Ardèche, France), adjacent to the fires, were very high (> 300–375°C). In this sense, they propose that the purpose of these big fires could be related to functions additional to lighting, such as sanitation of the cavern, human protection from animals, smoke production without a direct practical need except in relation to the scenography of the decorated space, together with the voluntary modification of the coloration and consistency of the wall concerning the execution of Paleolithic art [ 21 , 22 , 49 ]. Likewise, they have developed some monitored experimental activities and numerical simulations of fires in caves [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notre-Dame of Paris, Deldicque & Rouzaud (2020)) or even natural caves (Carrancho et al 2009, Salmon et al 2019. Fires were ignited in a quarry situated in south-west France , Salmon et al 2020b), aiming at understanding the impact of Paleolithic fires on the Chauvet-Pont-d'Arc Cave walls (Ferrier et al 2017, Salmon et al 2020a.…”
mentioning
confidence: 99%